Línea de pobreza y salarios, 1913-1925. Una primera aproximación - Zegarra, Luis Felipe (2011)
This article relies on linear programming to calculate the extreme poverty line between 1913 and 1925. Using several sources, I estimate the minimum amount of income that a family had to earn in order to afford its basic feeding needs. Our estimations indicate that the minimum basket of foodstuff was afforded with a little more than a sol per day before the First World War, and that the cost of such basket increased to more than twice toward the end of the war. A comparison with the salaries of the period indicates that in Lima a large number of workers could afford the basket of basic foodstuff of their families, especially if more than one member of the family received wages; but that such ability largely declined by the end of the 1910s